Spiritualisme Zikrullah Pada Kepemimpinan Transformasional Dalam Membangun Karakter Peserta Didik - Ibnu Safii; Susanto; Akhmad Shunhaji (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The study explores the role of transformative leadership based on Zikrullah spiritualism in the context of Islamic education. Transformative leadership plays a crucial role in shaping student character, and this study seeks to explore how integrating spiritual values through Zikrullah can amplify the positive impact of such leadership. This thesis delves into the concepts of transformational leadership, Islamic spirituality, and Zikrullah, offering a comprehensive theoretical foundation. By examining these interconnections, the study aims to establish a framework that elucidates how transformational leadership, grounded in Islamic spiritual principles particularly the practice of Zikrullah can effectively foster the character development of students. This thesis covers the concepts of transformative leadership, Islamic spirituality, and the Zikrullah concept. This theoretical framework provides a basis for understanding the relationship between transformative leadership characterized by Islamic spiritual values, Zikrullah, and student character development. Research findings show that transformational leadership integrated with Zikrullah spiritualism has a positive influence in shaping the character of students. Positive changes include moral, ethical, personality and social adaptation aspects, which can strengthen students' moral foundations. The study uses a qualitative approach using observations, interviews, and document analysis. Study participants included school leaders, teachers, and students. This method is designed to gain an in-depth understanding of the implementation of transformative leadership based on Zikrullah's spiritualism and its impact on the student's character. Overall, this thesis concludes that transformational leadership based on Zikrullah spiritualism has great potential to improve the superior character of students. These findings not only contribute to understanding the concepts of leadership and spirituality in the context of Islamic education, but also provide practical insights for the development of character-oriented education policies in similar schools. Research findings suggest that the integration of transformative leadership with Zikrullah's spiritualism has a positive influence on student character formation. The presence of positive change includes moral, ethical, personality, and social adaptation aspects, which can strengthen the student's moral foundation. This research provides practical implications for education managers and leaders in Islamic schools. Integrating spiritual values into leadership an learning policies can serve as a basis for creating an educational environment that supports student character development. Overall, this thesis concludes that transformational leadership based on Zikrullah's spiritualism has significant potential to enhance the excellent character of students. These findings not only contribute to an understanding of the concepts of leadership and spirituality in the context of Islamic education, but also provide practical insights for the development of character-oriented education policies in similar schools.